Organizational Dissent Dynamics: A Conceptual Framework. (May 2017) - Zaini, Raafat Mahmoud; Elmes, Michael B.; Pavlov, Oleg V.; Saeed, Khalid
This article proposes a conceptual framework for dissent dynamics in organizations. We integrate the dissent expression and management framework of Kassing with the dynamic institution composition structure of Saeed and Pavlov to construct a generic model for understanding organizational dissent. Our model hypothesizes the impact of dissent accumulation on organizational dissent climate, composition, and performance. Two performance measures comprise the performance grid to describe the current state of an organization and its dissent management policies—perceived management responsiveness and organizational productivity. We argue that dissent expression, tolerance, and management policies affect whether an organization is high or low performing. The conceptual model provides a future platform for experimentation and learning by simulating different policy scenarios and their influence on the paths of change and the new homeostasis eventually achieved by the organization.